A perceptual evaluation of speech disorders in children with repaired unilateral cleft lip and palate in Hospital UniversitiSains Malaysia - Alam, Mohammad Khursheed; Zulkipli, Aimi Syahidah; Percival, Sandra Elizabeth; Haque, Sanjida (Bangladesh Journal of Medical Science, 2018)
Aims and objective: The purpose of this cross sectional study was to determine the types and severity of speech disorders in children with repaired unilateral cleft lip and palate (UCLP) in Hospital Universiti Sains Malaysia (Hospital USM) and describe the inter- and intra-judge reliability of perceptual evaluation of speech disorders using GOS.SP.PASS’98 and five-point rating scale. Four children with repaired UCLP with ages ranging from 8 years old to 12 years old were included in this study. Prior to data collection, participants were contacted through telephone call from the list of patients with UCLP obtained Combined Cleft and Craniofacial Deformity Clinic (Combined clinic) in Hospital USM, Kelantan from year 2013-2015 as well as from clinical records from the database of the Record Unit of Hospital USM from year 2003-2015. Following strict inclusion criteria participant has been selected. After that, history taking was first conducted with the participant’s parents, followed by collection of participant’s speech sample and finally concluded with oral motor examination. Results: Fifty percent of the speeh samples obtained from data collection were then duplicated for use in inter-rater and intra-rater reliability investigations. Exact agreement and kappa values were used for reliability measures. Seventy-five percent (3/4) participants exhibited speech disorders and 25% (1/4) participant had no evidence of speech disorder. The type of speech errors that occurred the most in the three participants were glottal articulations (39%), while the least speech errors includedlateralizations/lateral articulations (2%), backing to velar (1%), pharyngeal articulations (1%,) active nasal fricatives (1%) as well as nasal realizations of fricatives (1%). The severity of speech disorder ranged from some occurrences to occurring always or almost alwaysin the participants. Inter-judge reliability showed poor to slight agreement while intra-judge reliability revealed almost perfect agreement. Conclusion: The results obtained from this study were more or less similar to other studies conducted on the speech outcome of individuals with repaired UCLP.It is important that referrals be made to speech-language pathologists (SLPs) to evaluate the individuals’ speech outcomes even though surgical intervention has been provided to them to ensure a comprehensive management for the individual. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.470-478